An investigation of the relationship between organizational culture and the performance of construction organizations - Cheun, Sai On; Wong, Peter S. P.; L. Lam, Anna (Journal of Business Economics and Management, 2012)
The operation of organizations is very much influenced by their culture. Organizational culture (OC) has been defined as a pattern of basic assumptions that are manifested by the behavior of an organization. Positive OC is considered to be catalytic to performance enhancement. As construction aspires to be an efficient industry, this study aims to contribute in this regard by examining the relationship between organizational culture and the performance of construction organizations. Artifacts corresponding to OC identifiers and Performance indicators are short-listed from a literature review. These artifacts are arranged into constructs. The eight OC constructs are: Goal Clarity, Coordination and Integration, Conflict Resolution, Employee Participation, Innovation Orientation, Performance Emphasis, Reward Orientation and Team orientation. The performance indicator constructs are; Financial, Internal Business Process, Custom and Innovation & Learning. The artifacts were elaborated and operationalized for data collection. The constructs, as well as the OC-Performance relationship framework, were then analyzed and tested using Structural Equation Modeling. Innovation was found to be the most critical OC as far as performance of construction organizations is concerned. In today’s knowledge based society, innovative organizations have proved to be the performers. This timely finding highlights the need for a culture that fosters creativity and supports innovation.